The dyslexia-associated gene KIAA0319 encodes highly N- and O-glycosylated plasma membrane and secreted isoforms. - Velayos-Baeza, A; Toma, C; Paracchini, S; Monaco, A (Oxford University Press, 2008)
The KIAA0319 gene has been recently associated with developmental dyslexia and shown to be involved in neuronal migration. The deduced KIAA0319 protein contains several polycystic kidney disease (PKD) domains which may mediate the interaction between neurons and glial fibres during neuronal migration. We have previously reported the presence of several alternative splicing variants, some of which are predicted to affect the deduced protein. In this study, we over-expressed constructs containing the main form (A) and two alternative variants (B and C) of KIAA0319. We show that the full-length KIAA0319 (A) is a type I plasma membrane protein, a topology consistent with its proposed function in neuronal migration. The oligomeric status of KIAA0319 is mainly dimeric, and this condition depends on the cysteine-rich regions of the protein, especially the transmembrane (TM) domain and surrounding sequence. KIAA0319 is highly glycosylated in different mammalian cell lines. The central region including the PKD domains is N-glycosylated. Furthermore, a short fragment N-terminal to the PKD domains contains mucin-type O-glycosylation. The two alternative isoforms are soluble proteins lacking the TM domain and, interestingly, only isoform B is secreted. KIAA0319-deletion proteins lacking the TM domain were also secreted. These results suggest that KIAA0319 could be involved not only in cell-cell interactions, but also in signalling.